Mobile devices for developing nursing students' professional skills: scoping review - Angélica Oliveira Veríssimo da Silva; Cristina Maria Correia Barroso Pinto; Rui Marques Vieira (Universidade de São Paulo, 2024)
Objective: to map the scientific literature on the use of mobile devices to develop the professional skills of nursing students. Method: this was a scoping review guided by JBI recommendations. Six databases and gray literature were included. The selection of studies was carried out through individual and peer assessment. Data were extracted based on an elaborate script and presented in a descriptive, tabular and graphical format. Results: 264 studies were identified, of which 13 comprised the corpus of analysis. The studies were carried out mainly on the Asian continent. Interventions ranged from one to 12 weeks, with a predominance of the use of Apps. The skills addressed were mainly clinical skills, techniques and procedures inherent to nursing practice, followed by decision-making and problem-solving. Conclusion: the studies analyzed not only revealed the potential of mobile devices in the training context, but also highlighted their contribution to improving clinical capabilities, as they offer support for a more dynamic and effective approach to the learning process. The gap in knowledge appears in the still unexplored possibility of integrating different professional skills through a single digital educational tool.